Public attitudes and perceptions toward forest fire in Selangor, Malaysia - Nuruddin, Ahmad Ainuddin; Chong, Wan Sze (INSInet Publication, 2008)
This study attempted to assess the attitudes and perception of three groups of people affected by forest fire i.e public, fire fighters and villagers affected by forest fire. Likert questionaire is used to elicit repondents attitudes and perception by asking the degree to which the individual agree or disagree with the statement. Respondents from all three groups agreed that forest fire would cause air pollution, soil erosion, green house effect and thick haze, so indirectly cause disease like asthma, respiratory disease, skin infection. Villager affected by forest fire supported immediate fire suppression and agree that forest fire is a big problem in this country. However the public and fire fighter did not agree with this perception. The findings from this study will help the relevant authorities to formulate fire prevention and educational campaign.